Game-based cryptographic algorithms learning - Tan, Malcolm Wei Zhang (Nanyang Technological University, 2023)
In an ever-evolving landscape of digital communication, secure data transmission has become paramount. The art of encoding and decoding information plays a pivotal role in ensuring data confidentiality. This project introduces an innovative approach to cryptography education through a game-based application that explores classic encryption methods.This report serves as a comprehensive guide to the project, detailing software choices, components, and their functionality. It outlines the project’s objectives, scope, and the broader context of cryptography education.This project integrates modern user interface design principles to ensure a seamless and intuitive user experience while providing educational opportunities that sparks curiosity and engagement.